Penggunaan Compost Tea Diinduksi Inokulum Fungi Lignoselulolitik Pada Media Tanam Cocopeat Terhadap Pertumbuhan Tanaman Kailan (Brassica oleracea L.). - Sally Khoirunisa Sally Khoirunisa; Bambang Irawan; Rochma Agustrina; Endang Nurcahyani; Sri Wahyuningsih (Jurnal Penelitian Pertanian Terapan, 2021)
Compost tea is a compost extract that has many nutrients. In addition, the planting medium is also important in plant cultivation. Cocopeat is very suitable for growing media because it can store nutrients and water. The purpose of this study was to determine the effect of giving compost tea induced by lignocellulolytic fungi on cocopeat media on the growth of kailan (Brassica oleracea L.) and to determine the type of compost tea and the best media composition on the growth of kailan plants. This research was conducted from May to July 2020 in the greenhouse of the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The research was conducted factorial using a completely randomized design (CRD) consisting of 2 factors, factor I was compost tea (A) with 2 levels of treatment, namely: compost tea aeration (A1) and compost tea nonaeration (A2). The second factor is the planting medium (B) with 3 levels of treatment ratio, namely: cocopeat and soil with a ratio of 2: 1 (B1); 1: 1 (B2); 1: 2 (B3) to obtain 6 treatment units. The control was not part of the treatment but the control was included in the graph as a comparison between treatments. The treatment was repeated 4 times. The parameters observed were plant height. The measurement data obtained were tested by the ANARA test. If there are differences in treatment, continue with the Tukey's test. The results showed that compost tea aerated (ACT) gave a higher average yield compared to compost tea noneration (NACT) while the composition of the planting medium for cocopeat: soil = 1: 2 gave a higher average yield than other media compositions.